Cervical Cancer and Pap Smear Health Belief Level in Women Applying to Cancer Early Diagnosis Screening and Training Center - Çağla Yiğitbaş; Gülay Çelik; Aliye Bulut (Sakarya Tıp Dergisi, 2020)
Objective: This study was conducted to determine health belief levels of women who were living in a city center and applied to Cancer Early Diagnosis Screening and Training Center towards cervical cancer and pap smear tests and identify if the sociodemographic characteristics make a difference or not. Methods: The population of the study consisted of women who applied to Cancer Early Diagnosis Screening and Training Center located in Bingöl city center for routine screening. The study was completed with 188 women. Personal Information Form and Health Belief Model Scale for Cervical Cancer and Pap Smear Test were used to collect the data of the study. Results:According to the study results, it was determined that the women had the highest mean score in pap smear barriers subscale and the lowest mean score in the cancer sensitivity subscale among subscales of Health Belief Model Scale for Cervical Cancer and Pap Smear Test. Conclusions:Most of the women participating in the study had not heard of HPV and pap smear test before, and never had a pap smear test. In addition, having heard of HPV before and knowing and having the pap smear test increased pap smear and cervical cancer benefit perception and decreased the barrier perception. In this context, the most important factor causing barrier perception towards pap smear test and cervical cancer is the lack of knowledge of women on this issue. Therefore, informing and providing counseling about pap smear test and cervical cancer by healthcare professionals is believed to be important.